Pengaruh Lama Perendaman Dengan Perasan Jeruk Lemon dan Garam Dapur Terhadap Kadar Protein Tahu - Nastiti Kartikorini (Universitas Muhammadiyah Surabaya, 2017)
abstractTofu is one of the healthy foods because of the relatively high protein content. In know that stored at room temperature will only last for 1-2 days. Therefore, many sellers know who gives the formalin to preserve know. Whereas the use of formaldehyde is very harmful for health. One of the efforts to secure the preservation know that the provision of 10% lemon juice and salt to 4% who will preserve up to 6 days at room temperature. Just know that the old storage can cause denaturation of proteins which can result in decreased levels of protein out. This study aims to investigate the influence of soaking in lemon juice and salt to the protein content out. The protein content was obtained through laboratory know the Micro-Kjeldahl method. The sample was 8 were divided into 4 groups: control, know by soaking for 1 day, 3 days and 6 days. To determine the effect of soaking the protein content out statistical analysis used ANOVA and continued to LSD. The results of the data analysis ANOVA test showed that there was no effect of soaking time with the lemon juice and salt to the protein content of tofu (p values> 0.05). Average protein content know that soaked for 1 day 13.24%, 12.78% and 3 days 6 days 12.34%. So it can be concluded that aging out with lemon juice and salt has no effect on protein levels out. Therefore preservation know this way is relatively safe and does not reduce the levels of proteins out.Keyword : tofu, lemon, protein level